Imperatives of Negotiation in Managing Covid-19 Vaccination Hesitancy in Nigeria - NWANMERENI, Daniel; MUSAH, Oyakemeagbegha (PT. Keberlanjutan Strategis Indonesia, 2023)
Purpose: The paradoxical hesitancy to COVID-19 vaccination amidst the spread of the pandemic, especially the deadly Delta Variant, has remained a source of worry to the global community. Despite assurances of the safety and efficacy of the vaccines and the jabs being publicly administered on top of the Nigerian political hierarchy, COVID-19 vaccination has remained controversial in Nigeria. It appears that citizens' apprehensions about the side effects of the vaccines are yet to be overcome.Methodology:This study investigated the grounds for Nigerian citizens' hesitancy to COVID-19 vaccination. The study asked: What factors underlie Nigerian citizens' hesitancy to COVID-19 vaccination? The quantitative study combined Social Cognitive and Diffusion of Innovations theories as theoretical cornerstones. A survey research design was adopted to study a population of 84 004 084, from which a sample size of 384 respondents was drawn.Findings:The study's findings showed that the reported side effects of COVID-19 vaccines and citizens' distrust of the Nigerian government and health system led to COVID-19 vaccination hesitancy in Nigeria. NAFDAC's warning of fake COVID-19 vaccines being circulated in Nigeria was also found to be a factor that underlies hesitancy to vaccination.Implication:The study recommended, among other things, that national and international health authorities should address apprehensions generated by the reported side effects of COVID-19 vaccines. It was also recommended that Nigerian political leaders should rise to bridge citizens' distrust in the government.